2022
DOI: 10.1101/2022.12.09.22282977
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors Impacted on Wellbeing in Adolescent Who Have Family Member With Mental Disorder: A Literature Review

Abstract: Having a family member with mental disorder will affect their healthy family member life. This study to examine the factors impacted on adolescent well-being who have family member with mental disorder. This study was a literature review in two databases SCOPUS and Science which conducted by four steps: (1) identification of literature; (2) screening questions; (3) eligibility using inclusion criteria; and (4) assessment of the quality of the studies. This study found 17 article which then reviewed and analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…A review of 17 studies investigating the experiences of adolescents caring for family members with mental illness revealed that these teenagers regarded caregiving as a burden that caused them significant stress and negatively affected their quality of life and mental well-being. Furthermore, they experienced feelings of social isolation and a sense of being different from their peers of the same age [ 33 ]. Studies indicate that family members experience a sense of helplessness and a need for constant vigilance as a result of their lack of knowledge about the disease [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…A review of 17 studies investigating the experiences of adolescents caring for family members with mental illness revealed that these teenagers regarded caregiving as a burden that caused them significant stress and negatively affected their quality of life and mental well-being. Furthermore, they experienced feelings of social isolation and a sense of being different from their peers of the same age [ 33 ]. Studies indicate that family members experience a sense of helplessness and a need for constant vigilance as a result of their lack of knowledge about the disease [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%